CONSTITUTIONAL REFORMS IN PAKISTAN: TURNING AROUND THE PICTURE OF HEALTH SECTOR IN PUNJAB PROVINCE - Mazhar, Muhammad Arslan; Shaikh, Babar Tasneem (Journal of Ayub Medical College Abbottabad, 2016)
The 18th constitutional amendment in Pakistan requires an independent and objective analysis of consequences of 2011 reforms on the future roles demarcation between the federation and provinces for steering the health sector. The objective of this assessment study was to conduct an institutional appraisal of the provincial health department in Punjab to mark the achievements, problem areas and issues, as well as to formulate the recommendations in the post-devolution scenario. It was an in-depth literature review comprising papers found on PubMed/Medline, Google Scholar, reports published by the government departments, independent research works, academic papers, and documents produced by the development agencies in Pakistan, covering 18th constitutional amendment and its implications on health sector. Following 18th amendment, the Punjab Government formulated health sector strategy (2012-2017) which is being implemented in a phased approach. All districts have developed their three years rolling out plans. An integrated strategic and operational plan of MNCH, Nutrition and Family Planning is under review for approval. Punjab Health Care Commission has been established and is functional to regulate the health sector. Development agencies have in principle committed to support health sector strategy till 2017. Fair investments in improving governance, service delivery structure, human resource, health information, and medical products are expected more than ever in the post 18th amendment scenario. This is the chance for the health system of Punjab to serve the vulnerable people of the provinces, saving them from health shocks. Keywords: Reforms, Health system, Devolution, Pakistan